EFFECT OF METAL CITRATES ON INDICATORS OF THE EMBRYOTOXICITY OF CADMIUM SALTS IN RATS WITH COMBINED INTRODUCTION - Azarov, O.I.; Nefodova, O.O.; Halperin, O.I.; Solomenko, M.V.; Zhitniy, M.I.; Kononova, I.I.; Frolova, G.M. (World of Medicine and Biology, 2020)
The aim of the study was to determine the effect of metal citrates (cerium, zinc, iron) when combined with cadmium salts (chloride/citrate) on the embryotoxicity of cadmium in rats. The aim of the study was to determine the effect of metal citrates (cerium, zinc, iron) when combined with cadmium salts (chloride/citrate) on the embryotoxicity of cadmium in rats. Embryotoxic effects of test substances in groups were calculated and compared according to the following indicators: number of embryos, total, preimplantation, postimplantation embryonic mortality. Comparison of the embryotropic properties of cadmium chloride and cadmium citrate in the groups of isolated administration revealed a higher level of embryotoxicity of cadmium chloride. In the groups of combined administration, the greatest reduction in embryotoxicity was determined in the groups of the combination of cadmium with iron citrate for all studied indicators.
Keywords: embryogenesis; cadmium; cerium citrate; iron citrate; zinc citrate; embryonic mortality